Drilling of fibre reinforced plastic laminates - Durão, Luís M. (2014)
The use of fibre reinforced plastics – FRP’s – in structures is under a considerable increase. Advantages of their use are related with their low weight, high strength and stiffness. The improvement of the dynamic characteristics has been profitable for aeronautics, automobile, railway, naval and sporting goods industries. Drilling is a widely used machining technique as it is needed to assemble parts in a structure. This is a unique machining process, characterized by the existence of two different mechanisms: extrusion by the drill chisel edge and cutting by the rotating cutting lips. Drilling raises particular problems that can reduce mechanical and fatigue strength of the parts. In this work, quasi-isotropic hybrid laminates with 25% of carbon fibre reinforced plies and 4 mm thickness are produced, tested and drilled. Three different drill geometries are compared. Results considered are the interlaminar fracture toughness in Mode I – GIc –, thrust force during drilling and delamination extent after drilling. A bearing test is performed to evaluate tool influence on the load carrying capacity of the plate. Results consider the influence of drill geometry on delamination. A correlation linking plate damage to bearing test results is presented.